Respuestas

2013-01-21T23:34:05+01:00

 

sustituyendo

5(6+26)+1216+2(155)=

5(32)+1216+310=

160+1216+310=1686

 

7a+5b+3e(e+c)=

7(6)+5(26)+3(1216)(1216+155)=

42+130+3648(1371)=

42+130+5,001,408=5,001,580

 

3000-7a(a+b)=

3000-7(6)(6+26)=

3000-42(32)=

3000-1344=1656

 

10000-5(a+b)=

10000-5(6+26)=

10000-5(32)=

10000-160=9840

 

100000-{3(a+b)+5(b+e)]=

100000-{3(6+26)+5(26+1216)]

100000-{3(32)+5(1242)]

100000-{96+6210]=

100000-6306=93694

 

10000-{(a+b+c)+2(c+d)+e]=

10000-{(6+26+155)+2(155+913)+1216]=

10000-{187+2(1068)+1216=

10000-{187+2136+1216=

10000-3539=6461

 

20000-(10a+9b+8c)=

20000-(10(6)+9(26)+8(155))=

20000-(60+234+1240)=

20000-1534=18,466

 

espero no equivocarme al escribir, Saludos igual comprueba los resultados, suerte!!